Corrosion Analysis on Stainless Steel (SS304) Using A Coating Method Based On Silica from Natural Sand of Hukurila Village - Silahooy, Stevi; Branchiny Imasuly, Geovanny; Latuny, Wilma; Nggolaon, Delpina (Universitas Andalas, 2025)
Corrosion analysis was performed on stainless steel (SS304) coated with silica extracted from silica sand in Hukurila Village using the coprecipitation method. The XRF results showed an increase in silica content from 58.118% to 81.247%, indicating high purity. XRD testing revealed that the silica was amorphous, while SEM analysis showed that the silica powder particles were irregular in shape and size, and tended to undergo agglomeration. The silica was then applied as a coating on SS304 using Nippon Paint with silica-to-paint weight ratios of 95:5, 90:10, and 80:20. The samples were tested in a 3.5% NaCl solution for 7 days using polarization methods on a potentiostat to measure corrosion resistance. The results showed that the 80:20 weight ratio provided the highest improvement in corrosion resistance. This enhancement is attributed to the more compact and uniform coating structure formed at higher silica loading, which effectively minimizes micro-pores, strengthens the barrier effect, and suppresses localized pitting corrosion.